Genetic Diversity, Population Structure, and Linkage Disequilibrium in Bread Wheat (Triticum aestivum L.) - ALTINKUT UNCUOĞLU, AHU; AYDİN, YILDIZ (SPRINGER/PLENUM PUBLISHERS, 2016)
Bread wheat (Triticum aestivum L.) gene pool was analyzed with 117 microsatellite markers scattered throughout A, B, and D genomes. Ninety microsatellite markers were giving 1620 polymorphic alleles in 55 different bread wheat genotypes. These genotypes were found to be divided into three subgroups based on Bayesian model and Principal component analysis. The highest polymorphism information content value for the markers resides on A genome was estimated for wmc262 marker located on 4A chromosome with the polymorphism information content value of 0.960. The highest polymorphism information content value (0.954) among the markers known to be located on B genome was realized for wmc44 marker located on 1B chromosome. The highest polymorphism information content value for the markers specific to D genome was found in gwm174 marker located on 5D chromosome with the polymorphism information content value of 0.948. The presence of linkage disequilibrium between 81 pairwise SSR markers reside on the same chromosome was tested and very limited linkage disequilibrium was observed. The results confirmed that the most distant genotype pairs were as follows Ceyhan-99-Behoth 6, Gerek 79-Douma 40989, and Karahan-99-Douma 48114.
Keywords: Bread wheat; Microsatellite; Genetic diversity; Population structure; Principal component analysis; MAP; IDENTIFICATION; POLYMORPHISM; CULTIVARS; GENOTYPES; PATTERNS; DURUM